UPAYA MENINGKATKAN DISIPLIN GURU DALAM KEHADIRAN MENGAJAR DIKELAS MELALUI PENERAPAN REWARD AND PUNISHMENT SDN SARANG TIUNG KOTABARU (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2022)
Improving the quality of learning in schools is highly dependent on several factors. A very important factor, among others, is the application of school culture towards quality improvement. School culture is a positive thing that must be maintained and implemented by all school members without feeling forced. One of the school cultures that must be maintained is the issue of discipline, including the discipline of teachers in class attendance in the teaching and learning process. To improve the discipline of teachers can be pursued in various ways. In this School Action Research (PTS), an action was tried in the form of implementing Reward and Punishment for teachers at SDN Sarang Tiung, Kotabaru Regency. This research was carried out in two cycles, because from the results of research and data analysis, it turned out that in the second cycle, teacher discipline in class attendance in the teaching and learning process increased and met the predetermined indicators of 75%. From the results of this study, it can be concluded that to improve teacher discipline in class attendance in teaching and learning activities can be done by applying Reward and Punishment to teachers. Keywords: Teacher Discipline, Reward and Punishment, SDN Sarang Tiung